Vegetation Structure of Mangroves in Bagek Kembar, Sekotong, West Lombok - Cahyani, Vivi Maulida; Japa, Lalu; Santoso, Didik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Mangrove ecosystems play a crucial role in maintaining the ecological balance of coastal environments by supporting biodiversity and protecting shorelines. This study aimed to identify the species composition and analyze the vegetation structure of mangroves in the Bagek Kembar area, Sekotong, West Lombok, Indonesia. The research was conducted in January - May 2026 using a descriptive-exploratory approach with purposive sampling. Vegetation data were collected from 9 quadrats using line transect and quadrat methods. Data were analyzed using the species diversity index (H′), species evenness index (E), species dominance index (D), and Important Value Index (IVI). A total of 306 individuals belonging to five mangrove species were recorded, namely Avicennia marina, Rhizophora apiculata, R. mucronata, R. stylosa, and Sonneratia alba. The species diversity index (H′) was 1.30, indicating moderate diversity, the species evenness index (E) was 0.80, indicating high evenness, and the species dominance index (D) was 0.30, indicating low dominance. Rhizophora mucronata showed the highest Importance Value Index of 115.86, indicating its dominant ecological role in the mangrove community. These findings indicate that the mangrove vegetation in the Bagek Kembar area is in relatively good condition and highlight the ecological importance of the dominant species as a priority for conservation and sustainable mangrove ecosystem management.